(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Through the study of the physical variables of the study area, which lies in the south-western part of Baghdad governorate within the Mesopotamian alluvial plain, which represents the western part of the Unstable Shelf It has been shown that the electrical conductivity rate (EC) for a period of decrease and increase of water is Excessively Mineralized work. Whereas the pH, we find that the water of study area is neutral of pH during the two periods of the increases and decreases water. As for the water salinity (TDS), we find that the water of the study area is a Brackish water and for two periods increase water decreases. From the study of the hydrochemical variables for the studied area, we find that the sodium ion (Na+) is the common cation and sulfur ion (S-) is the common anion during the two periods which causing the total water hardness (TH). This refers that the water of studied area is very hard water for the two periods. In respect of the secondary elements we note that the nitrate ion concentrations were a few and have no effect on the powers of the water use for different purposes. The use of waters of the study area are unfit to drink human Depending on the Iraqi standard specifications (IQs, 2009) and the World Health Organization (WHO, 2007), we find that most of the water area suitable for the purposes of drinking animal and largely very good with the exception of magnesium ion (Mg) sulfates (So4) was a good degree as for electrical connectivity (Ec) it’s also very acceptable water can be used for all types of livestock, poultry and potentially diarrhea and my time. The use of water for irrigation purposes, we find that the value has exceeded salinity (2000ppm) and water study area can be used to irrigate the plants that bear high and that you need to experience salinity. As for the percentage of sodium ion (Na%), and depending on what the proposed (Scofield, 1935), the study area water can be used for irrigation purposes and do not cause damage to plants because the increase does not exceed (60%) except for wells (W1), which cause damage and cannot be used for irrigation purposes. As for the sodium adsorption ratio (SAR) and depending on the classification (Richard, 1959) note that all of the water adsorption ratio of the study area is less than 10 means that the water study area suitable for irrigation.